A review on pedestal waveguides for low loss optical guiding, optical amplifiers and nonlinear optics applications - Carvalho, Daniel O. [UNESP]; Kassab, Luciana R.P. [UNESP]; Del Cacho, Vanessa D. [UNESP]; da Silva, Davinson M. [UNESP]; Alayo, Marco I. (Elsevier, 2018)
In this work we review the recent advances and demonstrate possible future perspectives regarding pedestal waveguide fabrication technology. The optical waveguides produced using this technology represent a new platform to study novel optical materials that could not be explored differently as this fabrication process does not require etching of the core material itself. Thus, novel materials that are highly inert to chemical etchants, such as those composed of heavy metal elements, can be used with this new architecture that allows the fabrication of integrated optical devices. Lower propagation losses with pedestal waveguides when compared to rib waveguides are reviewed. The possibility to construct Mach-Zehnder interferometer structures using the pedestal waveguide technology is shown. The optical amplifiers with high gain are demonstrated using this pedestal process. Furthermore, using the pedestal architecture, it is presented the possibility to produce rare earth ions doped waveguides with gold nanoparticles, which demonstrated gain enhancement attributed to the efficient luminescence due to gold nanoparticles, thus opening possibilities for potential applications in integrated photonics. Finally, another research field that could benefit greatly in the near future from this new architecture is the integrated nonlinear optics as the pedestal waveguide fabrication technology opens up the possibility of using novel materials with high optical nonlinear susceptibilities.
Keywords: Gain enhancement due to gold nanoparticles; Integrated nonlinear optics; Optical amplifiers; Pedestal waveguides; Rare earth ions luminescence enhancement